Treatment with Anti-Sclerostin Antibody to Stimulate Mandibular Bone Formation - Tamplen, Matthew (Head Neck, 2018)
BACKGROUND: Anti-sclerostin antibody is a promising new bone anabolic therapy. While anti-sclerostin antibody stimulates bone formation and repair in the appendicular and axial skeleton, its efficacy in the craniofacial skeleton is still poorly understood. METHODS: Using an established model of Down syndrome-dependent bone deficiency, 10 Ts65Dn mice and 10 wild-type mice were treated weekly via i.v. tail vein injection with vehicle or anti-sclerostin for 3 weeks and sacrificed 1 week after. RESULTS: Wild-type mice treated with the anti-sclerostin antibody had increased mandibular bone, trabecular thickness, and alveolar height compared to controls. Anti-sclerostin antibody increased Ts65Dn mandibular bone parameters such that they were statistically indistinguishable from those in vehicle-treated wild-type mandibles. CONCLUSIONS: Treatment with anti-sclerostin antibody significantly increased mandibular bone mass and alveolar height in wild type mice and normalized mandibular bone mass and alveolar height in Ts65Dn mice. Anti-sclerostin antibody therapy represents a novel method for increasing mandibular bone formation.